ANALISIS PENGARUH TINGKATAN PROSES REBRANDING TERHADAP BRAND EQUITY BANK SULTENG KANTOR CABANG UTAMA - Aprianto, Aprianto (Katalogis, 2015)
The objectives of this research are: 1) to determine and analyze the simultaneous impact of rebranding process levels, which includes corporate rebranding, business unit rebranding, and individual products rebranding toward brand equity at Bank Sulteng Branch Office; 2) to determine and analyze the impact of corporate rebranding toward brand equity at Bank Sulteng Branch Office; 3) to determine and analyze the impact of business unit rebranding toward brand equity at Bank Sulteng Branch Office; 4) to determine and analyze the impact of individual products rebranding toward brand equity at Bank Sulteng Branch Office. This research is descriptive, which involves 100 respondents that are selected through proportional random sampling; the sample is selected by with accidental sampling method. The results imply that: 1) rebranding process levels, which includes corporate rebranding, business unit rebranding, and individual products rebranding simultaneously have significant impacts toward brand equity at Bank Sulteng Branch Office; 2) corporate rebranding significantly impacts brand equity at Bank Sulteng Branch Office; 3) business unit rebranding impacts brand equity at Bank Sulteng Branch Office; 4) individual products rebranding significantly impacts brand equity at Bank Sulteng Branch Office.